2010
DOI: 10.1002/mrc.2669
|View full text |Cite
|
Sign up to set email alerts
|

Difference between 2JC2H3 and 2JC3H2 spin-spin couplings in heterocyclic five- and six-membered rings as a probe for studying σ-ring currents: a quantum chemical analysis

Abstract: Adequate analyses of canonical molecular orbitals (CMOs) can provide rather detailed information on the importance of different σ-Fermi contact (FC) coupling pathways (FC term transmitted through the σ-skeleton). Knowledge of the spatial distribution of CMOs is obtained by expanding them in terms of natural bond orbitals (NBOs). Their relative importance for transmitting the σ-FC contribution to a given spin-spin coupling constants (SSCCs) is estimated by resorting to the expression of the FC term given by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In the context of this work, most important are more recent calculation results on the molecular fragments C−O−C−H and C−C−C(−O)−H . In turn, the 2 J CH values in a few heteroaromatic systems were subjected to a natural bond orbital (NBO) analysis . The NBO approach to n J CH values was also recently applied with the DU8c method, in which empirical scaling of the dominant FC terms in the formulated three multiterm predictive equations was performed by multivariate regression analysis.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…In the context of this work, most important are more recent calculation results on the molecular fragments C−O−C−H and C−C−C(−O)−H . In turn, the 2 J CH values in a few heteroaromatic systems were subjected to a natural bond orbital (NBO) analysis . The NBO approach to n J CH values was also recently applied with the DU8c method, in which empirical scaling of the dominant FC terms in the formulated three multiterm predictive equations was performed by multivariate regression analysis.…”
Section: Resultsmentioning
confidence: 52%
“…Hence, the two combined ranges of J CH values mentioned above could be used in the search for such an improvement. 5) Our best results for J CH values were found with the DFs rankedr ecently by Medvedev et al [66] as yieldingt he best electron-density distributions (APF-D (2), PBE0 (4) and mPW1PW91 (12), where the numbers are ranking positions of the 128 considered DFs) or affording small errors in chemically relevant density differences (insights from the Fukuif unction); [67] unfortunately,m PW1PW91 was not analyzed in ref. [67].I nt urn, M06-L,f ound here to be inappropriatef or J CH predictions, was ranked among the three DFs yielding the worst densities [66] or larger errors in the Fukui function.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This supports the assumption made above that a decrease in θ activates additional coupling pathways. By recalling that hyperconjugative interactions behave like carriers of the spin information associated to the FC interaction, , it is easy to observe the following additional coupling pathway σ C6–H6eq → π* C1O /σ C2–Cl2 → π* C1O ; see Table . This is similar to that of homoallylic 4 J CH SSCCs, and therefore, it should correspond to a negative contribution.…”
Section: Resultsmentioning
confidence: 99%
“…However, distance and geometry are not the only parameters that have influence over the J values. It was previously shown that the presence of heteroatoms in aromatic and non‐aromatic rings has a great influence on 2 J CH values. Nowadays, the application of Computer‐Assisted Structure Elucidation (CASE), algorithms to determine the 3D structures, is increasing, and according to authors it is not subject to the interpretational biases of human investigators .…”
Section: Introductionmentioning
confidence: 99%